ChemInform Abstract: 4‐CH3CONH‐TEMPO/Peracetic Acid System for a Shortened Electron‐Transfer‐Cycle‐Controlled Oxidation of Secondary Alcohols. Issue 43 (October 2015) - Zhang, Shufang; Miao, Chengxia; Xia, Chungu; Sun, Wei
Abstract The reagent system allows the oxidation of a wide variety of secondary alcohols into ketones under mild, metal‐free conditions.